A high-fidelity wave-to-wire model for wave energy converters. (April 2019) - Penalba, Markel; Ringwood, John V.
Abstract: Mathematical models incorporating all the necessary components of wave energy converters (WECs) from ocean waves to the electricity grid, known as wave-to-wire (W2W) models, are vital in the development of wave energy technologies. Ideally, precise W2W models should include all the relevant nonlinear dynamics, constraints and energy losses. This paper presents a balanced W2W model that incorporates high-fidelity models for each conversion system, and can accommodate different types of WECs, hydraulic power take-off (PTO) topologies, electric generators and grid connections. The models of the different conversion stages presented herein are efficiently implemented in the W2W model using a multi-rate integration scheme that reduces the computational requirements by a factor of 10. Two W2W models, i.e. one with the constant-pressure hydraulic PTO configuration and one with the variable-pressure configuration, are compared in this paper. Results show that a higher PTO efficiency (30% higher for the constant-pressure configuration) does not necessarily imply a higher electricity generation (2% higher for the variable-pressure configuration), which reinforces the need for high-fidelity W2W models for the design of successful WECs. Highlights: The paper presents a novel high-fidelity wave-to-wire model. Multirate integration scheme reduces computational requirements by a factor of 10. The impact of different hydraulic system configurations is evaluated. Higher PTO system efficiency does not necessarily mean higher generated power. Wave-to-wire models are necessary to evaluate the holistic performance of WECs.